2017
DOI: 10.3174/ajnr.a5473
|View full text |Cite
|
Sign up to set email alerts
|

Leukoaraiosis Attenuates Diagnostic Accuracy of Large-Vessel Occlusion Scales

Abstract: Background and purpose Pre-hospital stroke scales may help identify patients likely to have large vessel occlusion (LVO) to facilitate rapid triage to thrombectomy-capable stroke centers. Scale misclassification may result in inaccurate decisions and possible harm. Pre-existing leukoaraiosis has been shown to attenuate the association between deficit type and stroke severity. We sought to determine whether leukoaraiosis affects the predictive ability of 5 commonly used LVO scales. Materials and Methods We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…If such diversion is to occur, is there a differential accuracy of field severity screening tools in younger vs. older patients? One recent study suggests in patients with leukoariosis, severity scores may be less accurate for detection of LVO ( 44 ). In addition, a newer trial (NCT02930018) is examining whether a novel neuroprotective agent can improve outcomes in patients undergoing thrombectomy for ICA or M1 occlusions.…”
Section: Future Directions and Unanswered Questionsmentioning
confidence: 99%
“…If such diversion is to occur, is there a differential accuracy of field severity screening tools in younger vs. older patients? One recent study suggests in patients with leukoariosis, severity scores may be less accurate for detection of LVO ( 44 ). In addition, a newer trial (NCT02930018) is examining whether a novel neuroprotective agent can improve outcomes in patients undergoing thrombectomy for ICA or M1 occlusions.…”
Section: Future Directions and Unanswered Questionsmentioning
confidence: 99%
“…29,30 Furthermore, WMH has been shown to affect the clinical presentation in the setting of acute cerebral ischemia. 12,[31][32][33][34] Specifically, we previously demonstrated that among stroke patients with similar functional deficit severity at the time of their presentation those with a high WMH lesion burden had significantly smaller infarcts. 32 Accordingly, in the setting of a high WMH lesion burden smaller infarcts under the detection limit of MRI 35 would be expected to produce typical TIA deficits that can be more easily recognized as a probable TIA as determined by existing guidelines or the PREDISC scoring system.…”
Section: Discussionmentioning
confidence: 97%
“…In comparison, the Vision, Aphasia, Neglect (VAN) stroke assessment does not require score calculation or motor severity testing. Although initially published as an ELVO nurse triage in the emergency department (ED), 15 VAN has since been validated in multiple external EMS and hospital datasets [16][17][18] but has yet to be studied in a prospective prehospital EMS cohort.…”
Section: Ischemic Strokementioning
confidence: 99%